Co-digestion of garden waste, food waste, and tofu residue: Effects of mixing ratio on methane production and microbial community structure. Issue 5 (October 2021) - Song, Yingjin; Meng, Shuyan; Chen, Guanyi; Yan, Beibei; Zhang, Yingxiu; Tao, Junyu; Li, Yihang; Li, Jinlei
Abstract: Anaerobic mono- and co-digestion of three feedstocks (garden waste, food waste, and tofu residue) were investigated under mesophilic conditions by biochemical methane potential assays. The digestion performance of mono-substrate at different substrate/inoculum (S/I) ratios (2:1, 1:1, 1:2) and the synergistic effect of co-digestion with different feedstock' mixing ratios were evaluated by the modified Gompertz model and co-digestion performance index (CPI). The microbial community structure was analyzed to clarify the functional microorganisms in the digestion process. Results showed that the methane yield of different substrates for mono-digestion increased with decreasing the S/I ratio. Compared with the rapid decrease in pH of the mono-digestion of food waste and tofu residue, co-digestion could alleviate acidification and improved the buffering capacity of the system. As the feedstocks' mixing ratios changed, either synergistic (CPI = 1.09) or antagonistic effects (CPI = 0.89) might occur. Methane yield was the highest (370.54 mL/g VS) when the mixing ratio of garden waste, food waste, and tofu residue was 3:4:3. The modified Gompertz model fitted the experimental data well and revealed that the increase of garden waste had a considerable effect on shortening the lag phase due to the avoidance of rapid pH reduction. The microbial community structure changed with the substrate addition. Increasing food waste and tofu residue contributed to the enrichment of Methanosarcina . The composition of the archaeal community, especially the proportion of Methanosaeta, altered with the garden waste ratio. Graphical Abstract: ga1 Highlights: Anaerobic mono- and co-digestion of GW, FW, and TR were conducted. Garden waste could withstand a higher S/I ratio than food waste and tofu residue. Changing substrate mixing ratios caused synergistic or antagonistic effects in AD. Increasing garden waste significantly shortened the lag phase of co-digestion. The addition of GW changed the archaeal community structure in co-digestion.